Los siete sabios de Grecia. Enfoque Crítico - Conejo A., María Esther (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2015)
Many texts from the ClassicalAntiquity mention the "Seven Greek learned men". However, the real number oflearned wise accepted as such was much larger. This article proves that there always existed, at a given moment, a list of seven which changed according to place and epoch.• The lists also varied for posterity depending on the source and on the degree of distance in time. The author defines a small number of names found-in most lists and, tnerefore, considered the basic of all of them.